Blockchain in sheet metal processing. - Lechner, Michael; Christ, T.; Frey, Philipp; Wituschek, Simon; Arzhanov, A.; Petrov, F.; Merklein, Marion (wt Werkstattstechnik - Online, 2020)
The ability to both track physical products and to gather a production data record are important elements of modern manufacturing processes and crucial requirements for an end-to-end digital production. This work presents a solution for both challenges based on the combination of two systems: While a blockchain-based data exchange platform ensures that the requirements towards networked processes are met, an optical technology for marker-free identification of component parts is used.
CRIS-Team Scopus Importer:2021-04-19